Pengembangan Kemitraan dan Pemberdayaan Masyarakat melalui Pembibitan Pepaya (Carica papaya L.) di Desa Bojong - Muhammad Gian Gianggi Pratama; Belia Elgasari; Bonjok Istiaji; Yayat Hidayat; Suwarto; Willy Bayuardi (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The Calina variety of papaya (Carica papaya L.) is a fruit plant has a wide and varied range of markets, ranging from traditional to modern. Papaya seedlings are expected to produce highquality, high-productivity papayas that fulfill future demands on the export market. This community service activity in Bojong Village in Cilimus District aims to make the village a central production of Calina papaya seeds. In addition, the use of greenhouses that is less than optimal encourages maximum re-use to obtain good seeds, and the use of plastic cups as a medium for seeding papaya as an effort to prevent waste. The activities consisted of three series, including making Calina papaya cultivation modules, socializing Calina papaya cultivation, and practicing Calina papaya nurseries in a greenhouse using plastic cups. Keywords: Calina papaya, cultivation, nurseries